Review and evaluation of existing vulnerability indicators for assessing climate related vulnerability in Africa - Nathalie Jean-Baptiste; Christian Kuhlicke; Anna Kunath; Sigrun Kabisch (Helmholtz-Zentrum für Umweltforschung (UFZ), 2011)
The report provides a first theoretical setting on the concept of vulnerability, vulnerability assessment and indicators in order to identify and evaluate relevant assessment measures for the CLUVA project. It describes a set of identified indicators which serves as a starting point for selecting appropriate indicators for assessing climate related vulnerability. This is a contribution to the process of evolution of vulnerability assessment measures and to ensure a more robust and sustainable results in CLUVA. This report should therefore be seen as an initial conceptual proposition which needs to be tested empirically, peer-reviewed and discussed among experts, PhD candidates and practitioners working in the field of risk and vulnerability assessment. Only then can it be refined and fed back for further conceptual development.
Keywords: 330; Klimaveränderung; Risiko; Sozialer Indikator; Afrika